2019
DOI: 10.11144/javeriana.umed60-3.sabe
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities between Women and Men Aged Over and Under Seventy Years. SABE Colombia – Survey on Health, Well-being and Aging 2015

Abstract: Introduction: The differential approach by generation and gender, known inequalities and inequities to identify in older adults help in the evaluation of conditions and the design of interventions, research and teaching. Objective: Identify the peculiarities and inequalities related to generation and gender in the Colombian population of older adults. Methodology: Observational, descriptive and analytical study that performed a secondary analysis of the population survey SABE-Colombia 2015. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
0
0
2
Order By: Relevance
“…22(2): 1-15, mayo-agosto de 2024 y desplazamiento. Ello, desde un análisis de los determinantes sociales, lleva a peores desenlaces en salud y a un proceso de envejecimiento no saludable, lo que les confiere mayor riesgo de desarrollar síndromes geriátricos, como lo es la fragilidad (26).…”
Section: Discussionunclassified
“…22(2): 1-15, mayo-agosto de 2024 y desplazamiento. Ello, desde un análisis de los determinantes sociales, lleva a peores desenlaces en salud y a un proceso de envejecimiento no saludable, lo que les confiere mayor riesgo de desarrollar síndromes geriátricos, como lo es la fragilidad (26).…”
Section: Discussionunclassified
“…Aunque hacer una medición del maltrato a personas mayores presenta diversas dificultades por los instrumentos de medición y tipos de estudio, se estima que su prevalencia en la comunidad de Norteamérica y Suramérica oscila entre el 2,2 % y el 44,6 % (43). Estas condiciones adversas, violencias y maltrato fueron más evidentes en determinados grupos poblaciones, como se encontró en un análisis secundario del estudio SABE Colombia, en el cual se documentó cómo las mujeres mayores tuvieron menos oportunidades académicas, económicas y sociales durante su juventud, y ello llevó así a que haya mayor prevalencia de mujeres analfabetas, menor acceso a pensión, mayor índice de pobreza y mayor exposición a hechos de violencia respecto a los hombres ancianos colombianos (9,44).…”
Section: Tabla 1 Clasificación De La Violencia Según El Autor Y La Naturalezaunclassified
“…TB has been declared a priority in public health, where its common denominator is the inequitable distribution in the population and its overlap in regions with less development, in which it is important to address inequalities in women 7 . Studies in Colombia regarding gender gaps have shown that for women there are marked inequalities regarding their own income, economic participation rate, wages, among others 16,17 .…”
Section: Introductionmentioning
confidence: 99%